Pengetahuan dan Tingkah Laku Seks yang Berkait dengan Jangkitan HIV/AIDS di Kalangan Pelajar Institusi Pengajian Tinggi Awam - Mahamood, Yahaya; Ching, Tan Ching (ANIMA Indonesian Psychological Journal, 2002)
One hundred and twenty students were randomly assigned to a survey on knowledge and high risk HIV/AIDS sexual behavior. Data were collected through a set of questionnaires from students (N = 120; 60 males and 60 females), and analysed with t-test ANOVA and Pearson product moment correlation to determine the correlation between identified variables. In general, students have a good knowledge and decent sexual behavior. As such, there is no correlation between their knowledge and their behavior which could be infected with the HIV. There are more male students practicing high risk sexual behavior compared to female students. Sexual knowledge of the students didn't depend on sex, ethnicity, and study program. Ethnicity and study program didn't differentiate the IPTA student's sexual behavior.